Clinical/Photographic/Scanning Electron Microscopy Analysis of Pit and Fissure Sealants After 22 Years: A Case Series - Sundfeld, D.; Machado, L. S.; Franco, L. M. [UNESP]; Salomao, F. M. [UNESP]; Pini, N. I. P. [UNESP]; Sundefeld, M. L. M. M. [UNESP]; Pfeifer, C. S.; Sundfeld, R. H. [UNESP] (Operative Dentistry Inc, 2017)
Pit and fissure sealant is a clinical technique adopted to prevent caries lesion development. Ionomeric and/or resin-based materials are commonly used for this purpose. This article presents a case series of sealed teeth with 22-year follow-up evaluated by clinical, photographic, and microscopic analysis. In 1992, sixteen patients (9-14 years of age) had at least three teeth sealed with one of the following materials: resin-modified glass ionomer cement (RMGIC, Vitrebond or Fuji II LC) or polyacid-modified resin composite (PMRC, VariGlass VLC), totaling 86 sealed permanent teeth. After 22 years, 10 patients were recalled, representing 41 teeth. The retention of sealants was assessed by three methods: clinical analysis by visual inspection; photography; and scanning electron microscope (SEM) images and classified as retained (pits and fissures filled by sealant material); partially retained (pits and fissures partially filled by sealant material); or totally lost (no material was found in pits and fissures). The SEM images provided a higher number of retained sealants when compared with the clinical and photographic evaluations. Also, no totally lost scores were found with SEM analysis, regardless of the sealing material. No caries lesions were found. A fully or partially retained sealant in pits and fissures was capable of preventing caries lesions after 22 years within the patient pool analyzed.